Chile Fiscal Policy Management - Piasecki, Ryszard; Betancourt, Erico Wulf (Comparative Economic Research. Central and Eastern Europe, 2013)
A budget surplus arises in a country when the total revenue earnings surpass expenditures in a particular financial year. Having a budget surplus is very important in the sense that it brings about a decrease in the net public debt, while the public debt is increased in the event of a budget deficit. Both budget deficits and budget surpluses also exert indirect influences on taxpayers. Normally, it is not essential on the part of the government to maintain a budget surplus, though it needs to be very careful when running a budget deficit to have the proper buffer.